Pengaruh Rotasi, Reputasi dan Spesialisasi Auditor terhadap Kualitas Audit (Studi Empiris pada Perusahaan Manufaktur yang Listed di BEI) - Adib Azinudin Nizar (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The study aimed to empirically examine the effect of auditor rotation, audit reputation, and audit specialization on audit quality. The population of data is the entire manufacturing companies listed on the Indonesia stock Exchange in the period 2012 to 2015. Based on this method, sample of 104 manufacturing firms were obtained from the period 2012-2015. Proxy measurements for audit quality are using earning benchmark. The logistics regression was used to analyse data. The results showed that auditor rotation affecting on audit quality, auditor reputation affecting on audit quality, and auditor specialization affecting on audit quality.Keyword: auditor rotation, auditor reputation, auditor specialization, audit quality.